Early safety outcome following transcatheter aortic valve implantation: is the amount of contrast media used a matter of concern? (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: The study objective was to evaluate the impact of the amount of contrast medium used for transcatheter aortic valve implantation (TAVI) on short-term outcome. Patients undergoing TAVI are exposed to repeat contrast medium application both for preprocedural screening and during the TAVI procedure itself. Whether the amount of contrast media is associated with worse outcome is unclear. METHODS: A total of 257 patients were included (median age 82.7 years) and divided into two groups with preserved and reduced kidney function (glomerular filtration rate